An observational study of lower limb muscle imbalance assessment and gait analysis of badminton players - Huang, Ping; Xu, Wenxin; Bai, Zeyi; Yu, Lin; Mei, Qichang; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2024)
Lower limb muscle imbalance can cause gait abnormalities and increase the risk of muscle injury or decreased performance in significantly asymmetrical situations. This study aims to assess the lower limb muscle imbalance and gait feature between the dominant and non-dominant sides of badminton players and the associations between the two variables. The study included 15 badminton players with years of training experience. Muscle strength and gait parameters were obtained from isokinetic muscle strength testing and plantar pressure analysis systems. The symmetry index was calculated based on formulas such as plantar pressure distribution and percentage of plantar contact area. In the isokinetic muscle strength test, significant differences were found in bilateral knee flexors' average power and total work at 60°/s angular speed. The hamstring to quadriceps ratio (H/Q) range of knee joints of the dominant and non-dominant sides is 0.63~0.74 at low speed, while the H/Q range is 0.81~0.88 at fast speed. The H/Q of bilateral knees increases with increasing angular velocity. As the angular velocity increases, the peak torque to body weight ratio (PT/BW) of the participants' bilateral knee flexors and extensors shows a decreasing trend. The asymmetry score of H/Q at 180°/s angular speed is positively related with step time and stance time. There are varying degrees of differences in gait staging parameters, plantar pressure in each area, plantar contact area, and symmetry index between the dominant and non-dominant sides of badminton players when walking. Badminton players have weaker flexors of the knee joint, imbalanced muscle strength in flexors and extensors, decreased lower limb stability, and a risk of knee joint injury on the nondominant side. The bending and stretching strength of the knee joint on the dominant side of the players is greater than that on the non-dominant side. The pressure in the first metatarsal region of the dominant side is higher, while that in the midfoot and heel regions is higher on the non-dominant side. badminton players have better forward foot force and heel cushioning ability. Long term badminton sports result in specialized changes in plantar pressure distribution and reduced symmetry.